Effect of XlogP and hansen solubility parameters on the prediction of small molecule modified docetaxel, doxorubicin and irinotecan conjugates forming stable nanoparticles - Mei-Qi Xu; Ting Zhong; Xin Yao; Zhuo-Yue Li; Hui Li; Jing-Ru Wang; Zhen-Han Feng; Xuan Zhang (Taylor & Francis Group, 2021)
Small molecule-chemotherapeutic drug conjugate nanoparticles (SMCDC NPs) has a great advantage in improving drug loading. However, the factors which influence these conjugates forming stable nanoparticles (NPs) are currently unclear. In our previous studies, we synthesized a series of fatty acid-paclitaxel conjugates and suggested that the changes in the hydrophobic parameters (XlogP), solubility parameters and crystallinity of these fatty acid-paclitaxel conjugates were the key factors for affecting these small molecule-chemotherapeutic drug conjugates (SMCDCs) forming stable NPs in water. Here, we selected clinically widely used chemotherapeutic drug (docetaxel (DTX), doxorubicin (DOX) and irinotecan (Ir)) as model drug, and chose three straight-chain fatty acids (acetic acid (Ac), hexanoic acid (HA) and stearic acid (SA)) and one branched small molecule (N-(tert-butoxycarbonyl) glycine (B-G)) to synthesize 12 SMCDCs. Our results indicated that our prediction criterions obtained from paclitaxel conjugates were also appropriated for these synthesized SMCDCs. We suggested that the present studies expanded the scope of application of the above-mentioned influencing factors, provided research ideas for the rational design of SMCDC forming NPs and a basis for screening NPs with good anticancer activity.